Short-course preoperative radiotherapy increases pelvic fracture risk in rectal cancer - Väliaho Vesa; Mäkitalo Jaana; Kohonen Ia; Carpelan Anu; Minn Heikki; Ristimäki Raija; Ålgars Annika; Heervä Eetu (Elsevier Ireland Ltd, 2025)
Introduction
Pelvic insufficiency fractures (PIFs) are adverse events associated with chemoradiotherapy (CRT) administered preoperatively in rectal cancer, with incidences of 0–33.6% reported in the literature. Data on PIFs after 5 × 5 Gy fractionated short-course radiotherapy (SCRT) using highly conformal radiotherapy techniques such as volumetric modulated arc therapy (VMAT) is limited.
Methods
The Turku University Hospital colorectal cancer database was searched for patients operated on for stage I–III rectal cancer during the years 2014–2018. The hospital’s routine follow-up includes a 2-year computed tomography (CT) scan, which was systemically re-evaluated to detect PIFs. Only radiotherapy delivered using VMAT and image-guided approaches was included. Baseline demographics, tumor data, and dose-volume data were collected to identify risk factors for PIFs.
Results
Median time to CT scan was 24 months. Among the 164 patients analyzed, the 2-year PIF incidence was 22.2% for SCRT (n = 12/54, OR 9.1 (CI95% 1.9–42.9), p = 0.004), 9.1% for CRT (n = 4/44, OR 3.2 (CI95% 0.6–18.3), p = 0.13) and 3.0% (n = 2/66, reference) for those operated on without radiotherapy. The PIF incidence was not explained by differences in dose-volume data in either the SCRT or CRT groups. Fracture risk was higher in women, up to 50% after SCRT.
Conclusions
Every fifth patient treated with SCRT and rectal surgery presented with a PIF. Critical bony structures to be avoided during radiotherapy contouring could not be identified. Clinicians, especially those involved with the follow-up of rectal cancer, should be aware of this potentially debilitating and surprisingly common adverse event.